Analisis Daya Dukung Pondasi Tiang Menggunakan Metode Pile Driving Analyzer (PDA) (Studi Kasus: Jembatan Rengas, Kabupaten Batang Hari) - Raudhati, Emelda (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
Foundation as an important element to bear loads and transfer them to the ground. Foundation design considers various aspects, especially soil conditions, to ensure the bearing capacity and stability of the structure. The Pile Driving Analyzer (PDA) method is a testing technique used to assess the bearing capacity of pile foundations through dynamic load analysis. The analysis is performed using the "Case Method" for axial bearing capacity calculation, which is then analyzed using CAPWAP software, in accordance with ASTM D4945 (Standard Test Method for High Strain Dynamic Testing of Deep Foundations). The research was conducted at the construction site of the Rengas Bridge in Batanghari District, Jambi. The results show that the actual bearing capacity (Ru) of piles A1-P8 and A1-P9 are 137 tons and 270 tons, respectively, while the skin friction (Rs) values are 37 tons for A1-P8 and 103 tons for A1-P9. Additionally, the tip resistance (Rt) for piles A1-P8 and A1-P9 are 100 tons and 167 tons, respectively. The results indicate that pile A1-P9 has a higher bearing capacity compared to pile A1-P8, both in terms of skin friction and tip resistance, suggesting a significant difference in load-bearing capacity between the two piles.